Efficacy of single dose of misoprostol 800μg in the first trimester termination of pregnancy: a cross sectional study - Dakpe, Ronald; Basanti, Namoijam; Singh, Yanglem Ajitkumar; Singh, L. Bimolchandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The MTP (Amendment) Act 2021 has allowed termination of pregnancy up to 24 weeks on only certain indications. Decision of two medical practitioners are required for termination beyond 20 weeks. Misoprostol is one drug used for medical termination of pregnancy. It can be used alone in single or multiple doses, or in combination with other drugs. The study was undertaken to determine the efficacy of a single dose of 800 μg of misoprostol in the first trimester pregnancy termination. Methods: It was a cross-sectional study conducted among 124 women in the first trimester who were undergoing termination of pregnancy. After administering 800 μg of misoprostol vaginally, participants were kept under observation for 48 hours. Data were collected and analysed. Results: Around half of the participants (56.4%) expelled the conceptus completely by 12 hours, 78.2% by 48 hours. Seven (5.6%) out of those 27 failed cases were given further doses of misoprostol, while in the remaining 20 (16.1%), surgical intervention was undertaken. Conclusions: The efficacy of a single dose of misoprostol for 1st trimester termination of pregnancy varies widely from study to study, but, the efficacy increases with adding further doses of the same drug or addition of mifepristone. Misoprostol is a safe, cost effective, and reasonable drug for the termination of pregnancy in first trimester.